Design Defect Analysis of N-Lobed Non-circular Bevel Gear - Liu Qinqin; Lü Gang (Jixie chuandong, 2016)
To solve pitch curves of N- Lobed non- circular bevel gear being discontinuous,a novel pitch curve design method for non- circular bevel gear（ NCBG） is presented to simplify design of NCBG. The intersection curve equations between pitch cone surface of non- circular gear and spherical surface are derived,and the intersection curve is taken as pitch curve of NCBGs. The bevel gear with spherical involute is considered as generating cutter of NCBGs tooth profile,and mathematical models between pitch surface of bevel gear cutter and that of NCBGs are established. Based on this model,a machining simulation algorithm is developed. In addition,according to the characteristic of big end curve function of pitch cone surface of NCBGs,the causes of discontinuity and modifying methods of pitch curve of NCBGs are analyzed. The study results show that,the design defects such as undercutting and addendum overcutting of NCBGs can be identified quickly by applying the machining simulation algorithm,and it is exactly and effectively.